Subtract the untapped science of less - Leidy Klotz (New York, NY Flatiron Books, 2021)
Blending behavioral science and design, Leidy Klotz's Subtract: The Untapped Science of Less offers a scientific appreciation of why we underuse subtraction-and how to access its untapped potential. When humans solve problems, we overlook an incredibly powerful option: We don't subtract. We pile on "to-dos" but don't consider "stop-doings." We create incentives for high performance, but don't get rid of obstacles to our goals. Whether considering a stack of Legos, preparing a grilled cheese sandwich, or writing an essay, Leidy Klotz shows that we consistently overlook the principle of subtraction as a way to improve. Our mental preference for addition-for adding to what's already there rather than thinking of taking away-is so wide-spread and strong that we would prefer to accommodate wrong ideas than simply remove them. Drawing from his own pioneering research and scientific research throughout history, Klotz examines cultural, political, and economic trends underlying our neglect of subtraction, asserting that we have billions of years of evidence showing that lifeforms are perfectly capable of subtracting to improve. Proposing a new way to frame our behaviors, Klotz shares thought-provoking examples and anecdotes to supplement his proven techniques on implementing a new perspective and understanding of subtraction. By learning to use the counterintuitive approach of subtracting, we can revolutionize not just our day-to-day lives, but our work across every field and industry. Subtract shows how this innovative approach to life is the key to unlocking our greatest potential"-- Provided by publisher.
Includes bibliographical references
Keywords: Self-actualization (Psychology)